2022
DOI: 10.1002/cnm.3577
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of a novel catheter for liver radioembolization

Abstract: Radioembolization (RE) is a medical treatment for primary and secondary liver cancer that involves the transcatheter intraarterial delivery of micron‐sized and radiation‐emitting microspheres, with the goal of improving microsphere deposition in the tumoral bed while sparing healthy tissue. An increasing number of in vitro and in silico studies on RE in the literature suggest that the particle injection velocity, spatial location of the catheter tip and catheter type are important parameters in particle distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Ortega et al. ( 2022 ) studied a novel type of catheter in which particles exit through the sides of the catheter. They found that such a catheter helps particles disperse over the vessel lumen more rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Ortega et al. ( 2022 ) studied a novel type of catheter in which particles exit through the sides of the catheter. They found that such a catheter helps particles disperse over the vessel lumen more rapidly.…”
Section: Resultsmentioning
confidence: 99%